Analisis Sistem Kinerja SIAKAD untuk Pembayaran SPP Mahasiswa pada STMIK Widuri dengan Metode PIECES - Veronika Natalia; Nur Nawaningtyas Pusparini; Sandri Sagitarius Sarumaha (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This research analyzes the performance of the Academic Information System (SIAKAD) in supporting student tuition payments at STMIK Widuri using the PIECES method (Performance, Information, Economy, Control, Efficiency, Service). SIAKAD aims to streamline academic administration and enable online payments. However, issues such as system access delays, especially near payment deadlines, still occur, negatively impacting students' academic services and resulting in administrative penalties. The study employed data collection techniques through observation, interviews, questionnaires, and literature review. The PIECES framework was applied to evaluate six key indicators: performance, information, economy, control, efficiency, and service. The findings reveal that all indicators achieved an average score above 3.80, indicating a